(untitled) (Jurnal Adhyasta Pemilu, 2021)
Election of regional heads (pilkada) simultaneously is one of the democratic parties in the regional autonomy regime that has been going on since 2015. In the implementation of the elections there is certainly the possibility of disputes over the results of the elections. During this time the dispute resolution over the results of the elections carried out by the Constitutional Court. From 2008 to 2019, 982 disputes over the results of the elections were handled by the Constitutional Court. However, based on Decision of the Constitutional Court No. 97/PUU-XI/2013 stated that the addition of the authority of the Constitutional Court to adjudicate disputes over the results of local elections is an unconstitutional act. Then in Law No. 8 of 2015 concerning Pemilukada in Article 157 stipulates that the resolution of disputes over the results of the elections will be carried out by a special judicial body. In the law stated that the special judicial body was formed before the simultaneous election. Until now the special judicial body has never been realized even though the simultaneous local election has been rolling for 5 years. In this paper, we will discuss the urgency of establishing a special judiciary as an institution for the resolution of regional election disputes as determined by the Constitutional Court and the General Election Law. The method used in this study is the juridical method normative with the statutory approach and conceptual approach.